Smartphone Interrogation of Narrow Bragg Gratings in G.652 Fibre - Madeira Marcos; Santos Álvaro; Oliveira Valmir; Kalinowski Hypolito (EPJ Web of Conferences)
Transmission and reflection spectra of FBG in the visible region are seen and measured with a smartphone coupled portable apparatus. Standard G.652 optical fibre is used, operating in a few-mode regime.